2011
DOI: 10.1007/s00204-011-0782-2
|View full text |Cite
|
Sign up to set email alerts
|

Diverse effects of dimethyl sulfoxide (DMSO) on the differentiation potential of human embryonic stem cells

Abstract: In vitro disease modeling using pluripotent stem cells can be a fast track screening tool for toxicological testing of candidate drug molecules. Dimethyl sulfoxide (DMSO) is one of the most commonly used solvents in drug screening. In the present investigation, we exposed 14- to 21-day-old embryoid bodies (EBs) to three different concentrations of DMSO [0.01% (low dose), 0.1% (medium dose) and 1.0% (high dose)] to identify the safest dose that could effectively be used as solvent. We found that DMSO treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(138 citation statements)
references
References 18 publications
6
131
0
1
Order By: Relevance
“…In the present study, DMSO reduced the expression of stemness-related markers, such as SOX2, in the human EC cells, while also reducing DNMT3L, which is a specific marker for human EC cells. DMSO is known to induce differentiation in ES cell lines (25,26). Together with the perturbed differentiation of the human EC cells observed in response to DMSO within the present study, the findings also support a role for DMSO in modifying the stemness characteristics of EC cells and in mediating differentiation from pure EC cells to the other phenotypic components, including teratoma, choriocarcinoma and yolk sac tumors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present study, DMSO reduced the expression of stemness-related markers, such as SOX2, in the human EC cells, while also reducing DNMT3L, which is a specific marker for human EC cells. DMSO is known to induce differentiation in ES cell lines (25,26). Together with the perturbed differentiation of the human EC cells observed in response to DMSO within the present study, the findings also support a role for DMSO in modifying the stemness characteristics of EC cells and in mediating differentiation from pure EC cells to the other phenotypic components, including teratoma, choriocarcinoma and yolk sac tumors.…”
Section: Discussionsupporting
confidence: 85%
“…The present study results indicated that DMSO can induce resistance to CDDP and can perturb the differentiation status of human EC cells. DMSO is frequently used as a solvent in biological studies and as a vehicle for drug therapies (25,26). Even if DMSO is used as a vehicle for other drugs, when these agents are used in combination with CDDP, DMSO could reduce the chemotherapeutic efficacy of human EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 The small-volume transfers enabled by ADE mitigate the impact of the use of DMSO on biological assays. DMSO is the routine solvent for pharmaceutical small-molecule compound collections; however, DMSO has been shown to induce a range of effects on cells, including differentiation, growth arrest, and reduced cell viability, [4][5][6] and DMSO tolerance in cell-based assays is typically 0.1% to 0.5% v/v. Miniaturization of assays into 384-well and 1536-well formats is also enabled.…”
Section: Introductionmentioning
confidence: 99%
“…The stimulation with BMP4 together with FGF2 has been shown to induce mesendodermal differentiation Another small molecule used for the hepatic differentiation is dimethylsulfoxide (DMSO). It was reported to have a dose dependent effect on the expression of a large number of genes 113 . In the past DMSO has been widely used for the cryopreservation of cells, but has recently been found to also affect the undifferentiated state of hESC 114 .…”
Section: Hepatic Differentiation In Conventional 2d Culturementioning
confidence: 99%